Red cell distribution width and mortality in pediatric sepsis - Devina, Trina; Lubis, Munar; Mutiara, Erna; Yanni, Gema Nazri; Saragih, Rina Amalia C.; Trisnawati, Yunnie; Lubis, Aridamuriany Dwiputri; Amelia, Putri (Paediatrica Indonesiana, 2017)
Background Red cell distribution width (RDW) is a hematological parameter routinely obtained as part of the complete blood count. Recently, RDW has emerged as a potential independent predictor of clinical outcomes in adults with sepsis. However, RDW as a mortality predictor in pediatric populations has not been well established. Objective To determine the relationship between RDW value and mortality outcomes in pediatric sepsis patients. Methods We performed a cross-sectional study of 40 consecutive pediatric patients with sepsis admitted to the PICU from December 2013 to March 2014. All patientsâ€™ RDW were collected within 24 hours of sepsis diagnosis. We determined the association between RDW and hemoglobin (Hb) using Spearmanâ€™s correlation. The RDW values of 11.5-14.5% were considered to be normal while those > 14.5% were considered to be elevated. We compared mortality and PICU length of stay (LoS) between the normal and elevated RDW groups using Chi-square and Mann-Whitney tests. Results The median age of patients was 34 months (range 2 months to 17 years). There were 28 (70%) male subjects. Subjectsâ€™ median RDW was 14.8% (range 11.2-27.8%) and was not correlated with Hb (r=0.056; P=0.73). Mortality rates in the normal and elevated RDW groups were 40% and 45%, respectively. There were no significant associations between RDW group and mortality (P=0.749) or PICU LoS (P=0.350). Conclusion Unlike in adults, RDW values are not correlated with mortality in pediatric sepsis patients.Â